RETRACTED: Analysis of the efficiency of drilling petrocom solution for primary exposure of production formation at the Bolshoy Olkhovsky field named after V.N. Vinogradov - Kolosov E.A.; Kazarinov Y.I. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001